2018
DOI: 10.3390/ijerph15061199
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Remanufactured Products in Yangtze River Delta of China: Present Status, Problems and Recommendations

Abstract: Exponential increase of used and scrapped products has aroused worldwide attention, with various coping strategies regarding environmental protection and resource reutilization being considered and implemented. Among these, remanufacturing, processing used products environmentally and restoring them to like-new conditions, is preferred by nations around the world. China has been committed to developing and advancing the remanufacturing industry along with its products since 2013, however only a few residents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Second, remanufacturers, governments, and other stakeholders should work to increase consumers' awareness of RMPs. Cao et al (2018) report that almost half of the consumers in China are unaware of RMPs. Furthermore, for the respondents who are aware of RMPs, 64% learned about these products from the internet and 39% from government advertisements, which indicates that remanufacturers' and government marketing activities are effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, remanufacturers, governments, and other stakeholders should work to increase consumers' awareness of RMPs. Cao et al (2018) report that almost half of the consumers in China are unaware of RMPs. Furthermore, for the respondents who are aware of RMPs, 64% learned about these products from the internet and 39% from government advertisements, which indicates that remanufacturers' and government marketing activities are effective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cao et al. (2018) found that almost half of the respondents in their sample of Chinese consumers had never heard of RMPs. However, consumers are not the only group unfamiliar with RMPs, as many Asian countries do not clearly distinguish between RMPs and used products (Kojima, 2017; Nasr et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Remanufacturing as a specific type of eco-efficiency technology, which recovers, processes, and sells like-new versions of obsolete products, is playing a paramount role in environmentally conscious industrial efforts [3,4]. A remanufactured product can match the quality and performance of a new product, while remanufacturing the used product reduces both resource depletion and negative environmental externalities [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Remanufacturing opens a new avenue for realizing Responsible Consumption and Production, which is one of the Sustainable Development Goals (SDGs) introduced by the UN. Compared with conventional manufacturing that aggravates resource depletion and environmental pollution, remanufacturing has a cost advantage of saving 40-60% energy and reduces negative environmental effects by decreasing ~70% water consumption and 80% emissions of air pollutants [3][4][5][6][7]. The remanufacturing practice could present both environmental and economic performances, as well as social benefits to its implementers [8,9].…”
Section: Introductionmentioning
confidence: 99%